A Symbol-by-Symbol Cooperative Diversity Scheme for Relay-Assisted UWB Communications with PPM - Abou-Rjeily, Chadi (2013)
Email Print Request Permissions In this paper, we propose a novel cooperation strategy for coherent Impulse-Radio Ultra-Wideband (IR-UWB) communication systems with one relay. While non-orthogonal cooperation in narrow-band wireless networks often requires deploying distributed space-time codes with joint encoding of several symbols at the source and relays and joint decoding of these symbols at the destination, the proposed non-orthogonal cooperation scheme constitutes the first known symbol-by-symbol-based scheme where cooperation is entirely realized within one symbol duration. This follows from the fact that the proposed strategy is adapted to the structure of the Pulse Position Modulation (PPM) that constitutes the most popular modulation scheme associated with UWB transmissions. We also propose a simple and efficient power allocation strategy that further boosts the performance of the proposed cooperation strategy. The error performance of the proposed scheme is evaluated analytically while simulations performed over the IEEE 802.15.3a UWB channel model are provided to support the theoretical results.